(untitled) (Bangladesh Journal of Public Administration, 2022)
A quantitative survey-based study was conducted to evaluate the job satisfaction level of newly recruited civil servants of Bangladesh whose service time is 1.5 to 5 years. A total of 225 civil servants from ten different cadres responded to the survey on fourteen different aspects of the job. An additional response was also taken to evaluate overall job satisfaction. The result of the study reveals that the newly recruited civil servants of Bangladesh are dissatisfied with eight different aspects of the job (salary, promotion policy, posting place, transfer policy, training facilities, foreign tour facilities, recognition for good work and participation in decision making). On the other hand, respondents are satisfied with the other six different aspects of the job (job security, job status, working environment, relation with boss, relation with colleagues and autonomy in work). But considering everything in account overall they are satisfied with their job. Cronbach’s Alpha test for data reliability shows that the data are reliable having Cronbach’s Alpha value of .830 whereas the normal Q-Q Plot of variables reveals that all the independent variables of job satisfaction are normally distributed. For Pearson Correlation, there exists a significant and positive correlation between job satisfaction and all the independent variables. The current study suggests that further studies are to be carried out to investigate the causes of job dissatisfaction in different aspects and to identify which aspects of the job contribute most to the job satisfaction of civil servants.